Hydrothermal treatment of palm oil empty fruit bunches: an investigation of the solid fuel and liquid organic fertilizer applications. Issue 6 (1st November 2016) - Novianti, Srikandi; Nurdiawati, Anissa; Zaini, Ilman Nuran; Sumida, Hiroaki; Yoshikawa, Kunio
ABSTRACT: In this study, the investigation of hydrothermal treatment (HTT) of palm oil empty fruit bunches (EFB) on both solid product and liquid residue characteristics was conducted. The effects of HTT were investigated at temperatures of 100, 150, 180 and 220°C with 30 minutes holding time. Hydrochars were characterized by elemental analysis, SEM, ash analysis and TGA, while liquid products were analyzed by micro- and macronutrient analysis, and germination test. The results showed that the HTT treated EFB has an increased carbon content, lowered ash content, and lowered deposition tendency compared to the raw EFB. Moreover, the maximum of 37% of nitrogen, 65% of potassium and less than 10% of phosphorus in EFB were solubilized into the liquid residue which positively correlated with the temperature. The produced liquid was found unsuitable as a fertilizer due to low pH value, low N content, and low germination index, hence needing improvement when applied as fertilizer. These results demonstrated the possibility of employing the HTT for producing solid fuel as well as nutrient cycling in the plantation.